Effects of exogenous agents on the action of Bordetella parapertussis heat-labile toxin on guinea pig skin. - Endoh, M (1990)
Injection of sonic extracts of Bordetella parapertussis into the shaved backs of guinea pigs produced hemorrhagic necrosis, which previously has been attributed to the action of heat-labile toxin. As heat-labile toxin was purified from this crude mixture, its ability to induce hemorrhagic lesions decreased significantly. However, ischemic lesions were apparent after injection of the purified toxin. These lesions, while not hemorrhagic in nature, were marked by erythema surrounded by a region in which the ischemia was apparent. Exogenous agents were found to alter the nature of the skin lesion induced by heat-labile toxin. The lipid A portion of endotoxin in combination with heat-labile toxin caused hemorrhagic lesions surrounded by a ring of ischemia, whereas bovine serum albumin increased the area of erythema. While the nature of lesions induced by heat-labile toxin was affected by exogenous agents, the diameter of ischemia produced by the toxin was found to be independent of the presence of these agents and was linear with toxin dose. These results indicate that induction of hemorrhagic necrosis may not be a reliable indicator of heat-labile toxin activity. Instead, measurement of the ischemic lesion produced by heat-labile toxin may be a useful assay for the toxin.